"Beam us up, Bgwëthnėnė!" Indigenizing science (fiction). (June 2020) - Topash-Caldwell, Blaire
The popularity of Indigenous-authored science fiction art, literature, film, and even video games has exploded in recent years. More than just a niche interest, these works have material effects on the possibilities young Indigenous people envision for themselves. Contrary to research on the negative effects of Native American stereotypes on youth, positive representations of Native peoples found in Indigenous science fiction portray alternative futurisms to those represented in mainstream science fiction. Developed in concert with traditional knowledge and value systems, alternative futurisms as depicted in Indigenous science fiction forefront Indigenous agency in a genre where Indigeneity is either absent or made irrelevant. This article investigates the ways in which Indigenous science fiction creators leverage traditional knowledge systems to paint a picture of Indigenous futures that depart from mainstream science fiction in material ways.